Condition-Dependent En Route Migration Mortality of Adult Chinook Salmon in the Willamette River Main Stem. (4th March 2017) - Keefer, Matthew L.; Jepson, Michael A.; Naughton, George P.; Blubaugh, Timothy J.; Clabough, Tami S.; Caudill, Christopher C.
Abstract: Episodically high adult mortality during migration and near spawning sites has hindered the recovery of threatened spring-run Chinook Salmon Oncorhynchus tshawytscha in Oregon's Willamette River basin. In 2011–2014, we assessed migration mortality for 762 radio-tagged adults along a ~260-km reach of the main stem of the Willamette River. Annual survival of salmon to spawning tributaries ranged from 0.791 (95% CI = 0.741–0.833) to 0.896 (0.856–0.926), confirming concerns about mortality in the migration corridor. In a series of general linear models, descaling, marine mammal injuries, and head injuries to adult Chinook Salmon were linked to reduced survival during migration to tributaries. Many injuries were minor (i.e., epidermal abrasions), which we hypothesize were unlikely to have caused direct mortality but may have increased salmon vulnerability to pathogens or other disease processes. Mortality in the main stem was not significantly associated with salmon body size, energetic status, sex, origin (hatchery, wild), river discharge, or water temperature metrics. The ~10–21% estimates of en route mortality in this study provide an important benchmark for the main stem of the Willamette River. The estimates complement ongoing efforts to quantify mortality of adult Chinook Salmon in Willamette River tributaries and after collection and transport to spawning sites above high-head hydroelectric dams. Received September 15, 2016; accepted December 1, 2016 Published online March 3, 2017